Tube Sedge-Based Poverty Alleviation Model of Thale Noi Community, Phatthalung Province - Aueaungkul, Apinan; Srichookiat, Sanit; Khemakhunasai, Pornpan; Sampantamit, Tiptiwa; Kaewsuksaeng, Samak; Jitnirat, Nattapong (Area Based Development Research Journal, 2023)
In the Thalenoi sub-district, Kuan Khanun district, Phatthalung province of Thailand, there resides a group of vulnerable individuals facing challenges such as limited access to education, low income, and scarce employment opportunities. Despite these difficulties, this group possesses valuable traditional knowledge and skills in the art of tube sedge weaving. Their primary source of income comes from producing and selling these bags to middlemen and their typical income is 200 Baht per day. To address the pressing issue of poverty within this community, a poverty alleviation model was devised, known as "Tube Sedge Weaving against Poverty." The central idea was to enhance the production skills of this group to create higher-quality products, thereby commanding better prices in the market. The "Krajood Wannee" community enterprise played a pivotal role in this endeavor, serving as mentors and providing standardized skill development opportunities to 41 members of this vulnerable group. This poverty alleviation strategy had a dual focus: 1) Enhancing Knowledge and Skills: The target group's capabilities in production and marketing were fortified, bolstering both their human and economic capital. This encompassed comprehensive skill and knowledge development in various areas, including crafting techniques, raw material preparation, natural dyeing processes, embroidery techniques, stitching bag handles, and ensuring product quality. Furthermore, the participants received training in marketing skills, covering aspects such as brand creation, logo design, content-driven marketing strategies, and the innovative approach of live-stream sales tactics, 2) Community Enterprise Establishment: The "Lenoi Craft" community enterprise was founded to unite vulnerable individuals and involve them in these training programs. Consequently, participants acquired advanced knowledge and skills in both production and marketing. As a result, noteworthy transformations occurred within the target group: six individuals became proficient product design trainers, 19 participants became skilled in raw material preparation, three excelled in natural dyeing, 16 mastered weaving, nine honed their embroidery skills, and another nine became proficient in quality inspection. These enhanced skills led to increased revenues, with unfinished bag sales to "Krajood Wannee" totaling 512,100 Baht and additional income from sales in department stores amounting to 164,626 Baht. The establishment of the "Lenoi Craft" Community Enterprise marks the inception of social opportunities, facilitated by various support mechanisms from the public sector, playing a crucial role in empowering Thai community enterprises and fostering economic growth.